A new race of sunflower broomrape (Orobanche cumana) with a wider host range due to changes in seed response to strigolactones. Issue 2 (March 2020) - Dor, Evgenia; Plakhine, Dina; Joel, Daniel M.; Larose, Hailey; Westwood, James H.; Smirnov, Evgeny; Ziadna, Hammam; Hershenhorn, Joseph
Abstract: Broomrapes ( Orobanche and Phelipanche species, Orobanchaceae) are obligate root parasites of dicotyledonous plants. This taxonomic group includes seven weedy parasites of agricultural crops that damage vegetables, sunflower ( Helianthus annuus L.), and legumes. Processing-tomato ( Solanum lycopersicum L.) fields in Israel have been recently found infested with a new broomrape, first identified as nodding broomrape ( Orobanche cernua Loefl.) based on its host. However, its morphology resembled the closely related sunflower broomrape ( Orobanche cumana Wallr.), an obligate parasite of sunflower. The new race ( CUCE ) parasitized sunflower, tomato, and tobacco ( Nicotiana tabacum L.) in vitro, in a polyethylene bag system and in pots. Its seeds germinated in response to strigolactones (orobanchol, 5-deoxystrigol, 2′-epiorobanchol, and GR24) and dehydrocostus lactone (DCL), whereas O. cumana seeds responded only to DCL and GR24, and O. cernua only to strigolactones. Based on morphological similarities with O. cumana, shared molecular markers with O. cumana, ability to parasitize sunflower and respond to sunflower-germination stimulants, it was concluded that CUCE is a new race of O. cumana, with a host range expanding to Solanaceae crops. While being an important noxious weed of sunflower, this new O. cumana race is currently spreading and posing a threat to processing tomato in Israel. This finding is an alarming indication that broomrapes can shift host range and that similar new races of O. cumana could potentially appear in other countries.